Pemilu Pros and Cons of the Hashtag Movement # 2019GantiPresiden as a Means of Campaigns in Elections - Fitri, Sherly Nelsa (Law Research Review Quarterly, 2018)
This study aims to discuss the hashtag that is currently being talked about in the social media movement # 2019GantiPresiden. This hashtag is associated with the type of black campaign. This legal research is normative legal research, which is a perspective and applied research. The legal materials are collected through document studies (literature study), using deduction techniques. It was found that this Movement was actually legitimate because it was the freedom of everyone to think but could be a part of the black campaign if it leads to character assassination and tends to slander and lies and accusations without evidence.